2020
DOI: 10.1111/tpj.14677
|View full text |Cite
|
Sign up to set email alerts
|

Rice siR109944 suppresses plant immunity to sheath blight and impacts multiple agronomic traits by affecting auxin homeostasis

Abstract: Plant small RNAs (sRNAs) play significant roles in regulating various developmental processes and hormone signalling pathways involved in plant responses to a wide range of biotic and abiotic stresses. However, the functions of sRNAs in response to rice sheath blight remain unclear. We screened rice (Oryza sativa) sRNA expression patterns against Rhizoctonia solani and found that Tourist-miniature inverted-repeat transposable element (MITE)-derived small interfering RNA (siRNA) (here referred to as siR109944) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 113 publications
0
29
0
Order By: Relevance
“…Consistently, mutation of G-protein γ subunit DEP1 can promote rice resistance to RSB (Liu et al 2020;Sun et al 2019;Sun et al 2020a). Furthermore, auxin application enhances rice resistance to sheath blight (Qiao et al 2020;Sun et al 2019). These results indicate that auxin signaling positively regulates RSB resistance and that application of auxin analogues might effectively protect field crops against the disease.…”
Section: Phytohormones and Transcription Factorsmentioning
confidence: 69%
See 1 more Smart Citation
“…Consistently, mutation of G-protein γ subunit DEP1 can promote rice resistance to RSB (Liu et al 2020;Sun et al 2019;Sun et al 2020a). Furthermore, auxin application enhances rice resistance to sheath blight (Qiao et al 2020;Sun et al 2019). These results indicate that auxin signaling positively regulates RSB resistance and that application of auxin analogues might effectively protect field crops against the disease.…”
Section: Phytohormones and Transcription Factorsmentioning
confidence: 69%
“…The small RNA targets F-Box domain-and LRR-containing protein 55 (FBL55) encoding transport inhibitor response 1 (TIR1)-like protein. The siR109944-overexpressing rice plants have a significantly enhanced susceptibility to R. solani, while FBL55-overexpression causes the transgenic plants to be more resistant to RSB (Qiao et al 2020). Additionally, multiple indeterminate domain (IDD) proteins including LPA1 (Loose Plant Architecture 1), IDD3 and IDD13 form a transcription factor complex and regulate expression of the auxin efflux carrier gene PIN-FORMED 1a (PIN1a) in rice through binding to its promoter (Sun et al 2019;Sun et al 2020a).…”
Section: Phytohormones and Transcription Factorsmentioning
confidence: 99%
“…Overexpression of siR109944 facilitates the growth of R. solani companying with reduced IAA accumulation, whereas overexpression of OsFBL55 significantly suppresses R. solani growth associating with increased IAA accumulation. Consistently, IAA application improves resistance to R. solani, suggesting that IAA positively regulates rice sheath blight resistance and siR109944 manipulates auxin signal pathway to negatively regulate rice resistance to R. solani (Qiao et al 2020). Furthermore, sRNAs derived from R. solani are also found to be involved in rice-R. solani interaction.…”
Section: The Involvement Of Srnas In Other Rice Diseasesmentioning
confidence: 80%
“…Moreover, 14 long siRNAs (lsiRNAs) in length from 25-to 30-nt and several sRNAs are also identified to be responsive to R. sonali. Among them, some siRNAs-target modules show a tight conversely co-expression relationship, including lsiRNA51031-Os08g15322, lsiRNA73750-Os09g14490, lsiRNA118183-Os08g06220, lsiRNA194568-Os06g38990, miR167h-OsARF8, miR171a-Os02g44360, and miR160c-OsARF10, suggesting their involvement in regulating rice response to R. solani (Niu et al 2018;Qiao et al 2020). Among these differentially expressed sRNAs, siR109944 is further proved as a negative regulator in rice resistance against R. solani.…”
Section: The Involvement Of Srnas In Other Rice Diseasesmentioning
confidence: 99%
“…[5][6][7] Based on our present study, we found that rice Touristminiature inverted-repeat transposable element (MITE)derived siR109944 suppressed plant immunity to sheath blight, and overexpression of siR109944 in Arabidopsis could enhance susceptibility to Rhizoctonia solani by modulating auxin homeostasis. 8 To explore whether overexpression of siR109944 enhanced the broad-spectrum immune response in Arabidopsis, the OE line with a higher expression level was selected for this study. 8 We first inoculated siR109944 OE and Col-0 WT seedlings with B. cinerea, a destructive fungus.…”
mentioning
confidence: 99%